2017
DOI: 10.3390/ijerph14040448
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Using Outdoor Fitness Equipment and How? The Case of Xihu Park

Abstract: Outdoor fitness equipment (OFE) placed in public parks has the potential to encourage physical activity. However, little is known about OFE users and use patterns. This study employed onsite and video observations of OFE usage to describe user characteristics and patterns in Xihu Park. Results indicate that OFE in this park attracted considerable use, particularly in the early morning and late afternoon. During these peak-hour observations, approximately 12 users per hour used the OFE, with the majority being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 44 publications
5
32
1
Order By: Relevance
“…The participants exercised on four OFE stations, namely the air walker, ski machine, waist twister, and double arm stretch, in a random order to control for the order effect. The four types of OFE were selected as they are the most popular among OFE users [ 38 ]. For the air walker and ski machine, the participants performed PA at three tempos, namely 80, 100, and 120 bpm.…”
Section: Methodsmentioning
confidence: 99%
“…The participants exercised on four OFE stations, namely the air walker, ski machine, waist twister, and double arm stretch, in a random order to control for the order effect. The four types of OFE were selected as they are the most popular among OFE users [ 38 ]. For the air walker and ski machine, the participants performed PA at three tempos, namely 80, 100, and 120 bpm.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] In fact, there are established approaches that can be used to track PA patterns amongst public park users. 28 Current evidence in this area demonstrates some promise as well as keen interest in using public parks to increase PA levels although there is not a clear model that should be emulated for optimal efficacy.…”
Section: Public Parks and Healthy Living -State Of Current Evidencementioning
confidence: 99%
“…24 Recently, outdoor fitness equipment spaces have emerged in public parks to promote active options, although there currently is mixed evidence with respect to the impact of the recreational environment model on increasing PA patterns. 22,[31][32][33] The efficacy of community gardens in promoting healthier food choices has also gained recent and growing interest. [34][35][36][37] Studies have shown promise in using a community garden to improve an individual's perception of food and dietary habits.…”
Section: Public Parks and Healthy Living -State Of Current Evidencementioning
confidence: 99%
“…Only four OGs [ 11 , 13 , 17 , 30 ] had some sort of instructional support for users. The finding of inadequate instructional support may provide a reason for current OG research demonstrating that users did not interact with the equipment with an adequate amount and intensity to achieve health benefits, although the usage rate of equipment was high [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An OG is environmental infrastructure in an open space or an area in a park that consists of a cluster of weather-resistant exercise machines or exercise stations that assist individuals to perform physical activity [ 11 , 12 , 13 ]. Some OGs were built to serve older adults [ 14 , 15 ]; some were designed to serve diverse population groups [ 10 , 16 ]; and some were built along with other recreation infrastructures (footpaths) to add diversity and intensity to users’ physical activity practice [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%